Capital city: London as a financial centre - McRae, Hamish; Cairncross, Frances (London : Eyre Methuen, 1973)
This book tries to show that there is a lot more to the City than share dealing.The authors describe in detail the operations of the banks, the stock market, the insurance world and other bodies that make up the world's largest international financial center.
Includes index
Includes bibliographical references.
usc 03/05/18
Loans
Keywords: Financial institutions; Finance; Banks and banking; 332.1094212